The role of feedback in supporting trainees who underperform in clinical environments - Ajjawi, Rola; Bearman, Margaret; Molloy, Elizabeth; Noble, Christy (Frontiers in Medicine, 2023)
Introduction: Underperformance in clinical environments can be costly and emotional for all stakeholders. Feedback is an important pedagogical strategy for working with underperformance – both formal and informal strategies can make a difference. Feedback is a typical feature of remediation programs, and yet there is little consensus on how feedback should unfold in the context of underperformance. Methods: This narrative review synthesises literature at the intersections of feedback and underperformance in clinical environments where service, learning and safety need to be considered. We do so with a critical eye towards generating insights for working with underperformance in the clinical environment. Synthesis and discussion: There are compounding and multi-level factors that contribute to underperformance and subsequent failure. This complexity overwrites simplistic notions of ‘earned’ failure through individual traits and deficit. Working with such complexity requires feedback that goes beyond educator input or ‘telling’. When we shift beyond feedback as input to processes, we recognise that these processes are fundamentally relational, where trust and safety are necessary for trainees to share their weaknesses and doubts. Emotions are always present and they signal action. Feedback literacy might help us consider how to engage trainees with feedback so that they take an active (autonomous) role in developing their evaluative judgements. Finally, feedback cultures can be influential and take effort to shift if at all. A key mechanism running through all these considerations of feedback is enabling internal motivation, and creating conditions for trainees to feel relatedness, competence and autonomy. Broadening our perceptions of feedback, beyond telling, might help create environments for learning to flourish.